+0

# Inverse of a quadratic equation when x = -2

+1
59
2
+71

"Given f(x)=-3x^2-7x+19 and g(x)=2x^2-4x-5 find the following:"
"e. g^-1(-2) ..... (Hint: There are actually two answers here.)"
I've tried using the formulas and steps I've been given to find inverses of linear equations as well as using the quadratic formula but nothing seemed to work for me and I have no clue what I'm supposed to do with this. Any help would be appreciated!

Aleguan  Nov 21, 2017
Sort:

### 2+0 Answers

#1
+79894
+3

g(x)=2x^2-4x-5

For g(x), write y

y =  2x^2 - 4x - 5   factor out the 2

y = 2 ( x^2 - 2x -  5/2)    divide by 2

(y / 2) =  x^2 - 2x - 5/2      comlplete the square on x

(y /2) = x^2 - 2x + 1  - 5/2 - 1       factor the first three terms andsimplify

(y/2)  = (x - 1)^2  - 7/2   add 7/2 to both sides

[y + 7 ] / 2  =  (x - 1)^2      take both roots

±√  [ ( y + 7) / 2 ]   =  x - 1      add 1 to both sides

±√  [ ( y + 7) / 2 ] + 1   =  x       swap x and y

±√  [ ( x + 7) / 2 ] + 1   =  y       for y, write  g-1(x)

±√  [ ( x + 7) / 2 ] + 1  = g-1 (x)

So

g-1 (-2)  =  ±√  [ ( -2 + 7) / 2 ] + 1  =   √ [5/2]  + 1     or   - √ [5/2] + 1

CPhill  Nov 21, 2017
#2
+71
+3

Thanks again man!! I at least had the right idea in one of my previous attempts but I think I screwed up the order of processes for myself. Anyways, you've helped me out a lot :D

Aleguan  Nov 21, 2017

### 16 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details